Ukrainian memes as a means of forming national resilience - Yurkovskyi, Denys (Young Scholars Grinchenko – Seton International Journal, 2025)
Modern interstate conflicts unfold not only in the military-political dimension but also in the informational one. The Russian-Ukrainian war is a clear example of a situation in which one party in the conflict uses propaganda resources on a large scale to gain victory over its opponent in its own informational space. At the same time, the Ukrainian internet audience demonstrates resilience to Russian propaganda by using content that, with slight modifications, mimics sources (images, videos, statements, etc.) and spreads massively online – memes. The article aims to define the role of memes that gained popularity among Ukrainian social media users during the Russo-Ukrainian war in shaping national resilience in the fight against Russian disinformation.